Genome resource banking in the family Felidae - S. Ya. Amstislavsky; V. I. Mokrousova; V. V. Kozhevnikova; E. A. Kizilova; E. Yu. Brusentsev; K. A. Okotrub; V. A. Naprimerov; S. V. Naidenko (Вавиловский журнал генетики и селекции, 2017)
Many of the extant Felidae species are endangered or vulnerable. Others being not endangered as a whole species contain endangered subspecies. Only a very few cat species, besides domestic cats, are not in the risk group. Cryopreservation of embryos and gametes is a modern approach for ex situ mammalian genetic resources conservation. Freezing of semen has been successfully applied to the domestic cat and to more than 25 wild members of this family. However, embryos/oocytes cryopreservation was successful for only a small number of felids. Domestic cat and four wild Felidae species produced offspring after cryopreservation and subsequent embryo transfer. Regarding freezing of oocytes, so far different cryopreservation methods are still being experimentally tried exclusively for domestic cat. Genome Resource Bank (GRB) containing frozen semen of Amur leopard cat, bobcat and Eurasian lynx was established at the Institute of Cytology and Genetics, Novosibirsk. As a result of this project, original methods of feline semen freezing have been developed; embryos of domestic cat have been successfully frozen as well. Approaches to freeze domestic cat’s oocytes have also been tried. During this work, we combined biological and physical methods. In particular, the process of freezing embryos and oocytes was monitored with Raman spectroscopy. Different methods of frozen-thawed spermatozoa and embryonic viability testing were used in this study, including vital staining and subsequent fluorescent and light microscopy, and heterologous in vitro fertilization.